معالم الصلح في السنة النبوية وتطبيقاته على المجتمع الليبي : دراسة تحليلية - سنوسي، امحمد محمد زيد (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2022)
This research focuses on highlighting the features of peace agreements models based on Sunnah, especially when dealt with various events in peace situations. Furthermore, Prophet came to show the concept of magistrates and the extent of its legitimacy, with clarification and knowledge of the types of peace and the benefits of magistrates, as well as knowing the reasons obstructing peace. In addition, the research aims to present an analytical study on the parameters of peace in the Prophetic Sunnah, to revive the Prophetic Sunnah in this aspect, and reach a set of rules on the side of peace in the Prophetic Sunnah, in order to be a reference in this section, and aims to reach the reasons obstructing peace in Libya with the development of proposed solutions. In explaining this, the researcher will follow several approaches, including: the inductive approach in order to collect and extrapolate the hadiths of the Prophet Muhammad, may Allah bless him and grant him peace, from the nine hadith books mentioned in the chapter on reconciliation in the Sunnah, and the critical approach; This is to find out the extent of the authenticity of the hadiths from their weakness. Thus, the analytical approach is taken in order to analyze these hadiths and analyze the questionnaire that was developed and distributed to find out these reasons, the purpose of arriving at general rules in the chapter of reconciliation and developing the proposed solutions. The researcher revealed that the most important of which are: that reconciliation in The Prophet’s Sunnah was based on firm and clear legal principles in the Noble Qur’an and the Prophet’s Sunnah and that the Messenger, may Allah bless him, and his honorable companions, in their behavior and actions, took into account the requirements of peace, which reconcile between people, and that the provisions of peace is referred to, in their entirety, to the rule of collecting the word, judging with justice and recommending good things. Therefore, must be applied in Libya because it is crucial. The state must intensify efforts in this regard. The ruling between the litigants must be fair and advisory.